2002
DOI: 10.2323/jgam.48.193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ozone treatment on cell growth and ultrastructural changes in bacteria.

Abstract: However, cell inactivation was not significantly observed at concentrations of 10 6 , 10 7 cfu/ml even after an exposure of 150 min. Ultrastructural changes of treated bacteria showed deformation, rough damage and surface destruction revealed by scanning electron microscopy. Some bacterial cells showed collapsed and shrunken patterns within 60 min and severe rupture and cellular lysis after 90 min of ozone treatment. This study supports the proposed mechanism of the bacteria inactivation by ozone that caused c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
102
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 28 publications
(24 reference statements)
6
102
0
9
Order By: Relevance
“…Ozone was detected spectrophotometrically in the discharge associated with this plasma discharge. Thanomsub et al [45] reported that levels of ozone less than 1 ppm can have bactericidal properties. While the results from that study indicate ozone at low concentrations can have antimicrobial properties, we believe that it does not contribute significantly to the overall germicidal capability of the nonthermal plasma discharge independently.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone was detected spectrophotometrically in the discharge associated with this plasma discharge. Thanomsub et al [45] reported that levels of ozone less than 1 ppm can have bactericidal properties. While the results from that study indicate ozone at low concentrations can have antimicrobial properties, we believe that it does not contribute significantly to the overall germicidal capability of the nonthermal plasma discharge independently.…”
Section: Discussionmentioning
confidence: 99%
“…Either the outer lipid membrane in Gram-negative bacteria or the peptidoglycan cell wall in Gram-positive bacteria is the first structure to be oxidized by the oxygen atom. After the membrane alterations, the successive bacterial inactivation is caused by a lysis reaction (Thanomsub et al 2002). The aim of this study was to evaluate first the direct effect of ozone as a gas in saline on bacterial survival either when bacteria are suspended in both pure physiological solutions or after addition of human plasma at various concentrations or in blood.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation causes cell lysis and prevents bacterial growth (Santos et al, 2007;Silva et al, 2009). Thanomsub et al (2002) found that the ozone treatment was able to modify and destroy the structure of Gram-positive and Gram-negative bacteria. After 30 minutes of ozone exposure, the number of bacteria in cultures of 10 3 , 10 4 , and 10 5 CFU/ml decreased.…”
Section: Discussionmentioning
confidence: 99%
“…However, at higher bacterial loads (concentrations of 10 6 and 10 7 CFU/ml), there was a gradual decline in the survival of the cells, but the ozone was not effective against all bacterial cells even after a longer treatment period (150 minutes). Adequate concentrations of ozone can effectively result in antimicrobial activity by destroying the bacterial cell membrane and resulting in intracellular leakage and cell lysis (Thanomsub et al, 2002).…”
Section: Discussionmentioning
confidence: 99%